Evaluation of performance, emission and combustion characteristics of diesel engine fueled with castor biodiesel. Issue 2 (4th March 2017) - Das, D.; Pathak, Vipul; Yadav, A. S.; Upadhyaya, Rohit
ABSTRACT: In this experimental study, castor biodiesel was prepared by a transesterification process using potassium hydroxide as a catalyst. This extracted biodiesel was used to conduct a series of tests on unmodified direct-injection (DI) four-stroke diesel engines in order to investigate the performance parameters, exhaust emission and combustion characteristics. Neat biodiesel and biodiesel blended with mineral diesel were compared with the baseline operation of the engine. It was concluded that the lower blends of biodiesel have higher thermal efficiency and reduced fuel consumption. The use of biodiesel in conventional diesel engines resulted in the substantial reduction in emission of unburned hydrocarbons, carbon monoxide and particulates with an increase in engine loading condition. Lower blend shows a delay in heat release as compared to higher blends. The results prove that the use of castor as biodiesel in CI engine is a reliable alternative to diesel.